2017
DOI: 10.1007/s00284-017-1271-5
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Potential of Haloarchaeal Pigment Bacteriorhodopsin for Future Electronics: A Review

Abstract: Haloarchaea are known for its adaptation in extreme saline environment. Halophilic archaea produces carotenoid pigments and proton pumps to protect them from extremes of salinity. Bacteriorhodopsin (bR) is a light-driven proton pump that resides in the membrane of haloarchaea Halobacterium salinarum. The photocycle of Bacteriorhodopsin passes through several states from K to O, finally liberating ATP for host's survival. Extensive studies on Bacteriorhodopsin photocycle has provided in depth knowledge on their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…5,6 Previous research with biomolecules like proteins has already been reported for the development of transistors, 7 memory devices, 8 biosensors, 9 and light-emitting diodes. 10 Resistive switching devices based on azurin, 11 silk fibroin, 12 egg albumin, 13 ferritin, 14 and bacteriorhodopsin 15 have also been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Previous research with biomolecules like proteins has already been reported for the development of transistors, 7 memory devices, 8 biosensors, 9 and light-emitting diodes. 10 Resistive switching devices based on azurin, 11 silk fibroin, 12 egg albumin, 13 ferritin, 14 and bacteriorhodopsin 15 have also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, biological processes are dynamic, efficient, and precise and hence can be used as biomimetic alternatives in the field of molecular electronics. , Previous research with biomolecules like proteins has already been reported for the development of transistors, memory devices, biosensors, and light-emitting diodes . Resistive switching devices based on azurin, silk fibroin, egg albumin, ferritin, and bacteriorhodopsin have also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Exposed to a hostile environment, halophiles evolved unique biomechanisms, which make them very exciting scientific objects. Probably, the most important is the example of bacteriorhodopsin – a photoactivatable retinal membrane protein with unique properties, including stability at high concentration of salt (up to 5M), protease resistance, tolerance to high temperatures (upto 140 °C when dry) 1 and to a broad range of pH (at least 3–10) 2 . Bacteriorhodopsin has become the most studied membrane protein, often serving as a “model” for all other membrane proteins (see for instance 3 – 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Under the illumination of blue light, M 410 can be directly converted back to bR 570 and the decay time is reduced from milliseconds to hundreds of nanoseconds which matches with the decay time from bR 570 to M 410 , resulting in accelerated photocycle and steady photocurrent. Under nature sunlight, bR performs its original photocycle, and it cannot realize the directly return to bR 570 from the M 410 through the shortcut . Besides, in some extreme conditions, such as the deep sea and polar night, light is not sufficient.…”
Section: Methodsmentioning
confidence: 99%